KONSEP PSIKOLOGI DALAM PERSPEKTIF ISLAM DALAM BUKU PSIKOLOGI KEPRIBADIAN ISLAM - Wulandarivis, Dewi (STAI Darul Qalam Tangerang, 2023)
The concept of Islamic psychology studies the uniqueness and patterns of human behavior and personality based on the Qur'an and Sunnah as an expression of the experience of interaction with oneself, the surrounding environment, and the spiritual realm, with the aim of improving mental health and the quality of diversity. Research is carried out using literature or literature to obtain data in compiling theories as a scientific basis by reviewing and examining the main issues from the supporting literature, whether in the form of books, notes, or research reports from previous studies. Based on the discussion that the Concept of Psychology in an Islamic Perspective according to Dr.Bambang Samsul Arifin, M.Si is Islamic Psychology studies human behavior related to the surrounding environment so that a person is aware of forming self-quality in a more perfect direction (insan kamil) and getting happiness living in the world and the hereafter. Awareness to form self-quality is a continuation after knowing human behavior that is relevant to developmental tasks and the values ​​contained in Islamic teachings as a whole or comprehensively (kaffah). This whole behavior leads to self-perfection to achieve happiness in wading through life. Received serious attention and in-depth study. This concept is expected to provide a solution to the problems of Islamic education in Indonesia. The purpose of Islamic perspective psychology is to study human behavior and changes in that behavior as a result of the process of educational hands and try to see how behavior must be changed and guided through education